MENTAL DISORDERS AMONG PATIENTS WITH MULTIPLE SCLEROSIS - A MINI REVIEW - Sternik, Martyna; Ćwirko, Hanna; Skrobarczyk, Adam; Ćwirko-Kuśnierz, Sara; Garlak, Urszula (International Journal of Innovative Technologies in Social Science, 2026)
Multiple sclerosis (MS) is an autoimmune neurodegenerative disease and a commonest cause of non-traumatic disability in young adults. It affects up to 2.8 million people globally. In addition to the symptoms directly related to the disease, patients with multiple sclerosis often experience various mental disorders. The aim of this narrative review is to summarize the most common mental health conditions associated with multiple sclerosis and to highlight their clinical relevance by analyzing articles found in the Google Scholar database. As the data show, mental illnesses such as depression, anxiety, bipolar disorders and psychotic disorders affect MS patients more often than the general population and negatively impact their daily life, reducing its quality. The development of these conditions appears to be multifactorial, involving neuroinflammatory and immunological mechanisms, structural brain changes, psychosocial stressors related to chronic illness, and potential adverse effects of disease-modifying therapies. Therefore, it is crucial to raise awareness of these disorders to diagnose the condition promptly and administer appropriate treatment as quickly as possible.